Pengaruh Pendidikan Kesehatan Terhadap Tingkat Pengetahuan Tentang Jajanan Sehat Anak Di SD ST Antonius VI Medan Tahun 2024 - Patricia Olivine Aprilis Hutapea (STIKES Columbia Asia Medan, 2024)
Snacks play an important role in providing energy and other nutritional intake for school-aged children. The type of research used in this research is a quasi experiment with a One Group Pretest Posttest design. The sample in this study was 30 people and the sampling technique used the Total Sampling technique. Data analysis using the nonparametric Wilcoxon Signed Ranks Test. Based on the results of the Wilcoxon Signed Ranks Test, the significance value was 0.00 with a significance value of <0.05. These results show that there is an influence of health education about healthy snacks on the level of knowledge of children at SD.ST.Antonius VI Medan in 2024. It is hoped that health services and community health centers will improve providing information and providing health education, especially about healthy snacks.